Contribution and Challenges of Nurses in Times of Covid-19: A Narrative Review of the Literature - Pavez-Lizarraga, A (UNIV ALICANTE, 2021)
The Covid-19 pandemic has put the leadership and practical experience of nurses to the test, and has made care visible as an essential issue for human life and global health. Objective. The purpose of this literature review is to reflect on the contributions and challenges of nurses in times of pandemic. Method. A literature review was carried out, using the Wos and SciencieDirect databases, searching for the keywords "nursing" AND "Covid-19" AND "disaster", then it was supplemented with other documents selected from various sources, mainly reports of international organizations that have been relevant in the nursing and public health work during the pandemic period. Results. 48 documents and articles that met the inclusion criteria were reviewed. Conclusions. The main contribution of nurses to the pandemic is related to the ability to form a large containment force against Covid-19, guided by compassionate care. While some challenges are self-care and planning for the recovery of the post-pandemic health system.